Estrategias de ajuste ante choques economicos de oferta y demanda: Resultados de una encuesta a empresas mexicanas - Paula Sanchez-Romeu; Ernesto Rattia-Lima (Banco de México, 2013)
– This paper analyzes the adjustment strategies used by some Mexican firms to face supply and demand shocks. The information is provided by a survey carried out in 2012 by Banco de M'exico among 1,138 firms from different sectors. The results show that the response of firms to both types of shocks is not symmetrical in general, and that firms react to these shocks combining adjustment strategies (mostly choosing to reduce costs) to smooth the pass-through to prices and production. Stronger competition makes firms use the adjustment strategies more intensively, and it encourages price flexibility. For all shocks, the costs more likely to be reduced are non-labor costs, followed by temporary employment. A high degree of competition and a high labor share make the pass-through of shocks to employment stronger. On the other hand, collective wage agreements smooth this pass-through. Nominal wage rigidity is evident in the presence of any shock.
Keywords: J30; J31; D21; D22; E3; 330; firms survey; price; cost; wage; and employment adjustment; supply and demand shocks; competition; Wage Dynamics Network (WDN)